Preliminary Study: Habitat Characteristics of Amorphophallus spp. to Support Cultivation Development in East Lombok - Janwar Wahyu; Arben Virgota; Sukiman Sukiman; Baiq Farista; Suripto Suripto (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
One type of the Amorphophallus genus that has high economic value is Amorphophallus Muelleri, which is known as the local name Porang. Porang tubers are used to obtain glucomannan which is widely used in the drug industry. Currently, many porang tubers come from the forest and have not been widely cultivated. In Lombok island of, several species of Amorphophallus spp are found. Therefore, a preliminary study of the habitat information of Amorphophallus spp. in East Lombok is urgently needed, especially in the Kokok Tojang sub-watershed. This study aims to determine the habitat of Amorphophallus spp based on actual and potential existence data. The method used in this study is a purposive sampling method, namely by looking for actual and potential locations where Amorphophallus spp.ÃÂ In this study, two types of Amorphophallus were found, namely A. paeoniifollius and A muelleri. Habitat characteristics of Amorphophallus spp described by soil and microclimate parameters. Soil parameters include soil moisture (15-70% and an average of 28.5%); Soil temperature (24-29 oC), soil fertility (ideal) soil texture (clay clay, sandy loam, and dusty clay), conductivity (0.07 Ã¢â¬â 0.52 mS/cm). Microclimate parameters measured include temperature (19.4 Ã¢â¬â 30.3oC), humidity (64.4% Ã¢â¬â 81.4%), light intensity (60.3 Ã¢â¬â 22526.8 lux).